The Influence of the Employment Contract System and Work Motivation on the Employees’ Performance of PT Busana Indah Global - Herdiyani, Ricka; Kharisma, Kharisma (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Competition in the current industrial era is growing rapidly which requires more effective and efficient human resources. Contract employees are one of the company management's strategies for reducing the company's labor costs, but on the other hand, contract employees object because of uncertainty about career paths. Therefore, companies need to pay attention to the level of job satisfaction of contract employees, which is the main factor driving employee morale, discipline, and work performance in supporting the realization of company goals. Several factors that can influence performance are work motivation. This research aims to determine the influence of the work contract system and work motivation on the performance of PT. Busana Indah Global. The sample for this research is active contract employees. The technique for sampling was purposive sampling. In this research, the author used a questionnaire as an instrument in collecting data using Likert scale measurements. The method used in this research is a quantitative method that requires data analysis using validation, reliability, and multiple linear regression tests. This research was conducted by distributing questionnaires to employees of PT. Busana Indah Global consisted of 97 samples with 30 questions. The research results show that work motivation influences employee performance at PT. Busana Indah Global with an influence of 56.1%, while the rest is influenced by other factors. In the calculation results using SPSS, the influence of work motivation has a significant value of 0.001 < 0.005, meaning that work motivation does have a significant influence on the performance of employees at PT. Busana Indah Global.